The role of dissolved carbohydrates in the northern Adriatic macroaggregate formation - Penna, Nunzio (Acta chimica slovenica, 2009)
Total dissolved carbohydrates and their monosaccharide and polysaccharide fractions were studied at a fixed sampling point in the northern Adriatic sea off Pesaro, Italy, in 2001 and 2005 when the macroaggregates were absent...
Keywords: Adriatic Sea; Gulf of Trieste; Jadransko morje; makroagregati; Naravni pojavi; sluzenja morja; Sluzenje morja; Tržaški zaliv